KONSEP, FILOSOFIS, DAN KEBIJAKAN FISKAL ISLAM DI INDONESIA - Rani Mariana (Jurnal Penelitian Hukum Galunggung, 2025)
Fiscal policy in Indonesia is generally based on the concepts of efficiency, equitable development, and macroeconomic stability. The goals are positive economic growth, expanding employment opportunities, improving public welfare, and maintaining economic competitiveness. The philosophy of fiscal policy in Indonesia is enshrined in the 1945 Constitution, which prioritizes the prosperity of the people. State financial management prioritizes the principles of accountability, transparency, and value for money. Furthermore, justice and equity in development are also the basis for preparing the annual State Budget (APBN). Fiscal policy is implemented through careful planning and management of the APBN to maintain fiscal sustainability, primarily through optimizing domestic revenues, rationalizing state spending, and prudently managing the budget deficit. Islamic fiscal policy instruments in Indonesia have been accommodated through regulations on zakat (zakat), waqf (waqf), and Islamic finance, although they have not yet been fully implemented. Islamic fiscal policy is aimed at achieving income equality and social justice, encouraging real sector-based growth, maintaining monetary stability, and improving public welfare. Thus, Islamic fiscal policy in Indonesia is expected to spur improvements in the welfare of the Indonesian people at both the macro and micro levels through the multiplier effect of sustainable economic development.